Penapisan Enzim Invertase dari Khamir Asal Nektar dan Madu Hutan - Nur Wahidatun Ni’matun Hasanah; Miftahul Ilmi (Fakultas Biologi | Universitas Jenderal Soedirman, 2020)
Yeast is unicellular eukaryotic microorganism and one of the main resources in of organic compound. The natural compounds produced by yeasts have high commercial value; one of the examples is enzyme. Enzymes are widely used in industrial production processes. The invertase enzyme has the ability to catalyze sucrose, and hydrolyze it into equimolar monosaccharides, D-glucose and D-fructose mixtures called invert sugar. Invertase itself is commonly found in various parts of plants wich has high carbon content. Honey and nectar are compounds that have high carbon contents. Very high glucose and fructose contents show high levels of sucrose hydrolysis, so it is possible to have high levels of invertase enzymes in honey and nectar. This study aims to perform screening of invertase enzyme from yeasts that isolated from the nectar and forest honey and to find out the optimum temperature and pH for the enzyme production. This research was conducted by isolating yeast contained in wild honey and flowers nectar. Then conducted by qualitative test with selective medium and benedict test method. Quantitative test of intervase unit activity measured by DNS method with OD 540 nm. Protein concentration measured by Lowry Method with OD 650 nm. From 47 isolats 16 isolates able for invertase enzymes production. Yeast isolat SG 3.2 unit activity is 0.222 U/ml and specific activity is 7.07 U/mg. Optimum production pH and temperature are 5 and 25°C, respectively.